Alcohol intake and semen variables: cross‐sectional analysis of a prospective cohort study of men referring to an Italian Fertility Clinic. (18th July 2018) - Ricci, E.; Noli, S.; Ferrari, S.; La Vecchia, I.; Cipriani, S.; De Cosmi, V.; Somigliana, E.; Parazzini, F.
Summary: Background: The association between alcohol intake and male reproductive function is still controversial. In the frame of a prospective cohort study, designed to investigate the relation between life style and fertility, we performed a cross‐sectional analysis of semen quality. Methods: Men of subfertile couples, referring to an Italian Infertility Unit and eligible for assisted reproductive techniques (ARTs), were asked about their lifestyle: BMI, smoking, caffeine intake, occupational and leisure physical activity (PA) and alcohol intake in the last year before ART procedure. Semen volume, sperm concentration, total sperm count and sperm motility were determined. Age, risk factors for impaired male fertility, caffeine, smoking, leisure PA, days of abstinence and daily calories intake were accounted for in the analyses. Results: Between September 2014 and December 2016, we enrolled 323 male patients, mean age 39.3 years. Thirty‐one (9.6%) were abstainers, 97 (30.0%) drank <1–3, 98 (30.3%) 4–7 and 97 (30.0%) ≥8 alcohol units per week. As compared to men drinking <1–3 units per week, median semen volume was higher in the 4–7 units/week group (3.0 mL, interquartile range, IQR, 2.0–4.0 vs. 2.4 mL, IQR 1.7–3.5), as well as total sperm count (87.9 mil/mL, IQR 20.2–182.1 vs. 51.5 mil/mL, IQR 15.2–114.7). Association with sperm concentration was also significant, with a U‐shaped trend in groups of alcohol intake. After adjusting for potential confounders, these relations were confirmed. Similar patterns were observed in subgroups of leisure PA and risk factors for impaired male fertility, although these estimates often lacked statistical significance, presumably because of low sample size. Conclusions: Moderate alcohol intake appears positively associated to semen quality in male partners of infertile couples undergoing ARTs.